If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + 3x) = 2x (5 * 4 + 3x * 4) = 2x (20 + 12x) = 2x Solving 20 + 12x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 20 + 12x + -2x = 2x + -2x Combine like terms: 12x + -2x = 10x 20 + 10x = 2x + -2x Combine like terms: 2x + -2x = 0 20 + 10x = 0 Add '-20' to each side of the equation. 20 + -20 + 10x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 10x = 0 + -20 10x = 0 + -20 Combine like terms: 0 + -20 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| A=(3.14)(9) | | 5(1-2x)=15 | | k/10=5 | | I=(6800)(0.54)(11) | | 15+6x-19=3x | | 7z+x=7z+3 | | 7t-t-8=5t-3 | | 3x+x-3=3x+2 | | 5x+12=3x-5 | | r-8.2=-7.6 | | 14+x=8 | | 4w=.3 | | 0x=-16 | | 71-x=2x | | 6h=73-46 | | 156-5x=6x+24 | | C=2(3.14)(9) | | 71/69=69x | | 57x+1=x | | 57x+1=69 | | 3y+4=10 | | -2(p-5)+7p= | | 244*x=59536 | | 216=45p | | 2+2x+4-3x+3=12 | | ln(x-13)-2ln(x+1)=-2ln(7) | | 4x+19=14x-19 | | 5e+65= | | x^2-72x+512=0 | | d+2=2d | | (8x-3)(8x-3)= | | d+2=d-8 |